PERAN DUNIA USAHA DALAM MENGURANGI ANGKA KEMISKINAN DI INDONESIA (Fokus Ekonomi, 2009)
There are many efforts to decrease the poverty in Indonesia. The large number of povertybecomes an invaluable issue for anyone who wants to get simphaty from the other parties. Thedecrease of poverty in indonesia is, as a matter of fact, the responsibility for all people, allelements should have the sense of resposibility to the wealth of the society, among them arecompanies or the business world through Corporate Sosial Resposibility (CSR) program. Morethan 40 million people in indonesia are poor. The government attention trough APBN has notsolved this problem significantly. Therfore, the role of private sectors to reduce the number of thepoor through Corporate Sosial Responsibility (CSR) is needed. The programs conducted by thegovernment are charity while the other one conducted by corporations are more directed toempower the surrounding society by doing comunity development as their role to decrease thenumber of poverty in Indonesia.Keywords: poverty, corporate sosial respinsibility, charity, community development, sustainabledevelopment